THEORETICAL APPROACHES AND PRACTICAL TECHNOLOGIES FOR DEVELOPING PSYCHOEDUCATIONAL LECTURES AIMING AT IMPROVING THE PSYCHOLOGICAL WELL-BEING OF WORKING WOMEN (Psychology Travelogs, 2024)
The article is devoted to the problem of increasing the psychological well-being of young and middle-aged working women. It is noted that one of the possible directions for solving this problem is psychoeducational lectures, which are aimed at increasing awareness of methods of self-regulation and overcoming stress. Such awareness will prevent emotional burnout and improve the quality of life. At the same time, it is important to clearly understand what basic theoretical approaches and practical technologies should be used to develop psychoeducational lectures aimed at increasing the psychological well-being of young and middle-aged working women. There is no ready-made answer to this question in existing modern scientific publications. The purpose of the article is to determine the basic theoretical approaches and practical technologies that can be used to develop psychoeducational lectures aimed at increasing the psychological well-being of young and middle-aged working women. An analysis of scientific research on the topic of psychological well-being of young and middle-aged working women was conducted, since studying this is key to creating effective approaches that take into account the specific needs of women in this category. It was concluded that the integration of client-centered, cognitive-behavioral approaches, mindfulness practices, and technologies for developing mental self-regulation can be the basis for developing psychoeducational lectures aimed at improving the psychological well-being of young and middle-aged working women. Such psychoeducational lectures can help women increase self-acceptance, reduce anxiety, and develop adaptive coping strategies. However, the question of the effectiveness of these psychoeducational lectures requires further empirical research.
Keywords: psychological well-being; working women; psychoeducational lectures; client-centered approach; cognitive-behavioral approach; awareness practices; self-regulation technologies